2018
DOI: 10.1093/jmcb/mjy051
|View full text |Cite
|
Sign up to set email alerts
|

A role for the Tgf-β/Bmp co-receptor Endoglin in the molecular oscillator that regulates the hair follicle cycle

Abstract: The hair follicle is a biological oscillator that alternates growth, regression, and rest phases driven by the sequential activation of the proliferation/differentiation programs of resident stem cell populations. The activation of hair follicle stem cell niches and subsequent entry into the growing phase is mainly regulated by Wnt/β-catenin signalling, while regression and resting phases are mainly regulated by Tgf-β/Bmp/Smad activity. A major question still unresolved is the nature of the molecular switch th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 56 publications
(113 reference statements)
0
20
0
Order By: Relevance
“…Therefore, it is rare to identify the regulators that could mediate the downstream molecules simultaneously during feedback regulation of TGF-β and BMP signaling pathways in the same cell type and tissue or during the same biological process. A recent study has reported that endoglin, a newly identified common noncanonical receptor for TGF-β and BMP signaling pathways, could regulate the activities of both signaling pathways [ 11 ]. However, little is known regarding whether the core members within the pathways could feedback regulate their signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is rare to identify the regulators that could mediate the downstream molecules simultaneously during feedback regulation of TGF-β and BMP signaling pathways in the same cell type and tissue or during the same biological process. A recent study has reported that endoglin, a newly identified common noncanonical receptor for TGF-β and BMP signaling pathways, could regulate the activities of both signaling pathways [ 11 ]. However, little is known regarding whether the core members within the pathways could feedback regulate their signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Feedback regulation is nowadays identified and defined as downstream signaling proteins that regulate the expression or activity of upstream signaling molecules directly or indirectly (via other regulators or signaling axis), which is also known as the main feedback model of TGF-β family signaling pathways [ 6 ]. The regulators involved in this feedback regulation progresses includes (i) miRNAs, such as SMAD4-miR-675-TGFBR1 [ 6 ], SMAD4-miR-425-TGFBR2 [ 7 ], SMAD4-miR-302-BMPR2 [ 8 ], and SMAD4-miR-24-3p-SMAD2 [ 9 ]; (ii) lncRNAs, such as SMAD2/3-lncRNA-MALAT1-TGFBR2 [ 10 ]; (iii) transcription factors (TFs), such as β-catenin (mediates SMAD4 induction of receptor) [ 11 ]; and (iv) transcriptional coregulators, such as Snail [ 12 ]. Additionally, the experimentally validated axes, including the SCF/STAT3 axis (mediates SMAD2 positive feedback regulation of TGF-β1) [ 13 ], SLIT2-Gremlin axis (mediates SMAD1/5/8/4 complex regulation of BMP2) [ 14 ], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new roles for ENG have been described in physiological contexts. For instance, ENG is necessary to maintain correct hair follicle cycling and proper stimulation of hair follicle stem cell niches [ 115 ]. Furthermore, ENG mediates the regulation of the thermogenic gene program of beige adipocytes [ 116 ].…”
Section: The Physiological Role Of Endoglinmentioning
confidence: 99%
“…Moreover, it has been reported that WNT/β-catenin signaling during the onset of the anagen phase is accompanied by the specific expression of TGFβ2, that regulates proliferation, differentiation, and extracellular matrix production of dermal fibroblasts [19]. The interplay between WNT/β-catenin and TGFβ/BMP/SMAD to regulate stem cell niche function has been also described in different adult tissues, including the hair follicle [20]. It can be hypothesized that the GAG matrix produced by dermal fibroblasts in response to TGFβ/BMP/SMAD signaling is an essential component in the regulation of the hair follicle cycle and, particularly, in the feedback modulation of WNT/β-catenin signaling.…”
Section: Resultsmentioning
confidence: 99%